(3GdKeQGJ GdTgjI ef GdahGcgI GdMehjIs - (3CHh HcQ Hf Ydj Hf YHO Gddg GdMehj GdCRQGQj, Jbj GdOjf GHf MLI,J (B837 (3g` s ((3eMeO Hf GdMSf GdhOj GdTGaYj s)
(3ChdgG (B:s
(3hHYO(B: (3agPg ChQGb aj QjGV GdCOH RGgQI LeYJgG dYdej Cf GdbQjMI aj gPG GdRef GdNGed, hGdaf GdcGSO de JUd Edi CcKQ ef gPg GdebGUO, hdcf fSLJ aj TYQj Ydi efhGd bhe MdhG HGdJhQjI CTYGQge s
(3BNQgG (B:s
(3MSf GHJOGA Hg CQLh GdJNdU ef fGQ GdLMje hgPG MSf eNJJe QLhJ HHQcI eeOhMgG MSf GdNGJeI Hefg hcQeg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B70 (3Hs
(3GfXQ GdLRA GdChd HQbe (B162 (3COHs
(3hGfXQ cPdc Lfi GdLfJjf JMJ Qbe (B1227s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B67 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B67s
Keywords: (3GdCOHs